Dialogical conversations on power abuse in couples treatment for intimate partner violence : a qualitative analysis of positions and dominance used in conversations - Keltikangas, Marju; Kulta, Heidi; Kyrö, Hanna (2014)
The purpose of this Master's thesis was to study what kinds of dialogical conversations on power abuse occur in couples treatment for intimate partner violence. The study was conducted with qualitative methods. The data of this study, 20 conversations between female clients, male clients and therapists, was collected from seven videotaped couples therapy processes. The criteria for choosing conversations were that the topic of the conversation was power abuse or violence and both partners participated in the conversation. The data was analyzed from social-constructionist viewpoint with a dialogical approach. The research method used in analysis was Dialogical Methods for Investigations of Happening of Change. Focus was in two features of dialogue: dominance use and positioning. During the dialogical conversations on power abuse, female clients, male clients and therapists used three forms of dominance: quantitative, semantic and interactional dominance. Male clients were quantitatively and interactionally more dominant whereas female clients used more semantic dominance. During the dialogical conversations on power abuse, both clients constructed different kinds of positions for themselves and their spouses. Positions were categorized with content analysis. Categories were named: 1) Perpetrator vs. Victim, 2) Unfairly treated vs. Difficult spouse, 3) Superior vs. Inferior, 4) Reliable expert vs. Untrustworthy source of information, 5) Strong agency vs. Weak agency, and 6) Denying responsibility vs. Acknowledging responsibility. It is concluded that the use of dominance and positioning acts reflect unequal power hierarchies in spouses’ interaction. Therapists had to balance between supporting and confronting dominance and positioning acts. The thesis produced new knowledge about positioning and dominance use in couples therapy for intimate partner violence that can enable the therapists to intervene them and to construct more dialogical and equal way to discuss.